2018
DOI: 10.1002/jpln.201700544
|View full text |Cite
|
Sign up to set email alerts
|

Soil salt and NaCl have different effects on seed germination of the halophyte Suaeda salsa

Abstract: Seed germination is a key life-history stage of halophytes. Most studies on seed germination of halophytes have focused on the effects of a single salt, while little information is available on the effects of mixed salt in the natural habitat. Due to the contribution of multiple ions in saline soil, we hypothesized that the effect of mixed salt on seed germination will differ from that of a single salt and the mechanism of how germination is affected will differ as well. The effects of mixed salt and NaCl on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…But there is no significant relationship between soil nutrients and density of seed bank. This are halfway similar to the results reported in the previous literature ( Li and Xu, 2009 ; Erfanzadeh et al., 2010 ; Bai et al., 2014 ; Gao et al., 2018 ). The primary reason is that the salinity can exert a main inhibiting effect on the growth and manifestation of the plant community in the estuary wetlands, thus further affecting the formation of the seed bank.…”
Section: Discussionsupporting
confidence: 92%
“…But there is no significant relationship between soil nutrients and density of seed bank. This are halfway similar to the results reported in the previous literature ( Li and Xu, 2009 ; Erfanzadeh et al., 2010 ; Bai et al., 2014 ; Gao et al., 2018 ). The primary reason is that the salinity can exert a main inhibiting effect on the growth and manifestation of the plant community in the estuary wetlands, thus further affecting the formation of the seed bank.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, there is no comprehensive analysis on germination responses of dimorphic seeds of S. salsa to light condition and different temperature regimes. Furthermore, S. salsa seeds used in germination studies are mainly from the humid regions and not mentioned the seed type ( Song et al, 2008 ; Gao et al, 2018 ). Thus, germination characteristics of dimorphic seeds of S. salsa to different environmental factors and seedling growth are not well recorded, especially for this species grown in arid saline soils.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cotton exhibits greater resistance to complex salt stress. Some studies have also indicated that the impact of salt in soil leachate on cotton seed germination is relatively minor [ 18 ]. Several factors may contribute to this variation.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to highlight that natural environments feature more diverse soil salt compositions, with various ions such as Na + , Ca 2+ , and Mg 2+ inter-acting among themselves. These interactions may potentially mitigate their impact on plants, and oxidative enzyme activity could exhibit distinct effects [ 18 ]. The selection of soil-extracted salts from natural saline soils for plant salt tolerance experiments is a deliberate choice aimed at achieving a more faithful replication of the salt stress effects under natural conditions.…”
Section: Introductionmentioning
confidence: 99%